1978
DOI: 10.1037/0022-3514.36.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Low-ball procedure for producing compliance: Commitment then cost.

Abstract: The low-ball technique, a tactic often used by automobile sales dealers to produce compliance from customers, was examined in a set of three experiments. In all three studies, a requester who induced subjects to make an initial decision to perform a target behavior and who then made performance of the behavior more costly obtained greater final compliance than a requester who informed subjects of the full costs of the target behavior from the outset. The low-ball phenomenon-that an active preliminary decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
177
1
11

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(193 citation statements)
references
References 20 publications
(14 reference statements)
4
177
1
11
Order By: Relevance
“…Other studies have found that the low-ball strategy is more effective than the foot-in-the-door method; the explanation being that the preliminary request is the target behavior. Cialdini, Bassett, Miller, and Miller (1978) assert that the results of their studies indicate that "the low-ball phenomenon is reliable, robust, and mediated by a commitment to an initial, uncoerced decision to perform a behavior".…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found that the low-ball strategy is more effective than the foot-in-the-door method; the explanation being that the preliminary request is the target behavior. Cialdini, Bassett, Miller, and Miller (1978) assert that the results of their studies indicate that "the low-ball phenomenon is reliable, robust, and mediated by a commitment to an initial, uncoerced decision to perform a behavior".…”
mentioning
confidence: 99%
“…Although both the foot-in-the-door and the low-ball techniques rely on the person performing an initial request, the difference between the two is that in low-balling the preliminary request is the target behavior itself. In the first low-ball experiment, Cialdini, Bassett, Miller, and Miller (1978) asked students to participate in an experiment taking place at the University at an unsocial time, i.e. 7:00AM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated the effectiveness of the low-ball technique in gaining compliance (e.g., Burger & Petty, 1981;Cialdini, et al, 1978;Guéguen, Pascual, & Dagot, 2002). It is clear that the low-ball technique is used in Mr. Big operations.…”
Section: Six Reasons Why the Mr Big Technique Is Inherently Flawedmentioning
confidence: 99%
“…The low-ball technique is when someone revokes an appealing offer once it has been accepted, and replaces the appealing offer with a less desirable one (Burger & Cornelius, 2003;Cialdini, Cacioppo, Bassett, & Miller, 1978;Cialdini & Goldstein, 2004;Cialdini & Trost, 1998). A number of studies have demonstrated the effectiveness of the low-ball technique in gaining compliance (e.g., Burger & Petty, 1981;Cialdini, et al, 1978;Guéguen, Pascual, & Dagot, 2002).…”
Section: Six Reasons Why the Mr Big Technique Is Inherently Flawedmentioning
confidence: 99%